Classical scholarship and its history from the Renaissance to the Present : essays in honour of Christopher Stray - Harrison, Stephen 1947-; Pelling, Christopher 1947- (Trends in classics - scholarship in the making, 2021)
It is unusual for a single scholar practically to reorient an entire sub-field of study, but this is what Chris Stray has done for the history of UK classical scholarship. His remarkable combination of interests in the sociology of scholars and scholarship, in the history of the book and of publishing, and (especially) in the detailed intellectual contextualisation of classical scholarship as a form of classical reception has fundamentally changed the way the history of British classics and its study is viewed. A generation ago the history of classical scholarship still consisted largely of accounts of particular scholars and groups of scholars written by other scholars from a broadly biographical and 'heroic individual' perspective. In these works scholars often sought to find their own place in the great tradition, choosing to praise or blame those whose work they admired or deprecated, and to identify with particular schools or trends, and there were few attempts to provide a broader and less prosopographical perspective. Almost all the chapters in the volume originated as papers at a conference in honour of the honorand, and have been improved both by discussion there and by the rigorous peer-review process conducted by the two experienced editors. It covers various aspects of classical reception, with a particular focus on the history of scholars, their institutions, and their writings; the main focus is on the UK, but there are also substantial engagements with continental Europe and (especially) the USA; the period covered runs from the Renaissance to the present. The cast contains a number of world-famous names. Unusually, the volume also contains an essay by the honorand, but we are very keen to include this, especially as it focusses on the topic of scholarly collaboration